Diurnal and Seasonal Variations of Particulate Matter Concentrations in the Urban Forests of Saetgang Ecological Park in Seoul, Korea - Hong-Duck Sou (MDPI AG, 2021)
Urban forests provide various ecosystem services. Although the function of reducing particulate matter (PM) in the city is known, research into the reduction of PM according to the type and structure of various forests is still needed. It is essential to study the characteristics of PM concentration in urban riparian forests, which are frequently used for outdoor walks in the COVID-19 era. In this study, the diurnal and seasonal changes in PM10 and PM2.5 concentrations were analyzed in urban forests with different structures in the riparian forests located in central Seoul. The PM concentration was found to be high regardless of the time of the day in forests with a developed canopy layer. Similar results were found before and after leaf emergence compared with the seasonal PM concentration. The results of this study highlight the need for planned and periodic management of the canopy layer and underground vegetation to prevent the PM trapping effect to ensure the safe use of riparian forests in cities.